The art of blocking ADP‐ribosyltransferases (ARTs): Nanobodies as experimental and therapeutic tools to block mammalian and toxin ARTs. (14th June 2013) - Menzel, Stephan; Rissiek, Björn; Haag, Friedrich; Goldbaum, Fernando A.; Koch‐Nolte, Friedrich
<x xml:space="preserve">Abstract</x> In 1901, the first Nobel Prize in Physiology or Medicine was awarded to Emil von Behring for his ground‐breaking discovery of serum therapy: serum from horses vaccinated with toxin‐containing culture medium of Corynebacterium diphtheriae contained life‐saving 'antitoxins'. The molecular nature of the ADP‐ribosylating toxin and the neutralizing antibodies were unraveled only 50 years later. Today, von Behring's antibody therapy is being refined with a new generation of recombinant antibodies and antibody fragments. Nanobodies, which are single‐domain antibodies derived from the peculiar heavy‐chain antibodies of llamas and other camelids, are emerging as a promising new class of highly specific enzyme inhibitors. In this review, we illustrate the potential of nanobodies as tools to block extracellular and intracellular ADP‐ribosyltransferases (ARTs), using the toxin‐related membrane‐bound mammalian ecto‐enzyme ARTC2 and the actin‐ADP‐ribosylating Salmonella virulence plasmid factor B toxin of Salmonella enterica as examples.